Effect of Rain on the Aerodynamic Performance of a Horizontal Axis Wind Turbine – A Computational Study - Douvi, iEleni; Douvi, Dimitra; Pylarinos, Dimitrios; Margaris, Dionissios (جامعة الوادي - university of el oued, 2021)
This paper analyzes numerically the impact of rainfall on the aerodynamic performance of a three-bladed Horizontal Axis Wind Turbine, with blades constructed by NACA 4418 airfoil. The simulations were conducted by the help of the commercial Computational Fluid Dynamics code, ANSYS Fluent 19.2. Firstly, the optimum geometry of the blade was designed with an application based on Blade Element Momentum theory. The Moving Reference Frame Model was applicated to simulate the rotation of the blades and the k-ω shear-stress transport turbulence model was added as well. The simulation of rain was accomplished by the Discrete Phase Model and the Taylor Analogy Breakup model was enabled to simulate droplets breakup. Three different rainfall conditions were studied, corresponding to Liquid Water Contents of 10g/m³, 30g/m³ and 60g/m³. The influence of droplet diameter on the aerodynamic performance of the blade was also examined. The results showed that the aerodynamic performance of the wind turbine is degraded in rain conditions, and the degradation is greater for higher values of Liquid Water Content and for larger diameter of water droplets.
Article
Keywords: Aerodynamic Performance, Discrete Phase Model, Horizontal Axis Wind Turbine, Rainfall.